Analisis dan Perancangan Usaha Pembukaan Cabang Baru pada Konveksi XYZ di Kota Bandung - Prame, Adinda; Chumaudiyah, Endang; Rendra, Meldi (IAI Nasional Laa Roiba Bogor, 2024)
Konveksi specific industry or agency. The problem with convection piling up and not making convection operational activities efficient. The aim of this study is to consider market aspects, technical aspects and financial aspects. By carrying out this feasibility analysis, convection can find out what needs to be prepared and know what risks will occur in order to avoid or minimize existing risks in the longer term. This financial aspect approach uses calculations of the Internal Rate of Return (IRR), Net Present Value (NPV), Payback Period (PBP), and Profitability Index (PI). The benefit of the proposed design results is that it can estimate the size of market demand for the opening of a new branch of XYZ Convection in Bandung City, namely 8,513 pcs in 2025, it can design the technical and operational aspects of opening a new branch of XYZ Convection in Bandung City by determining an investment of IDR 153,738,772, it can measure the financial feasibility of opening a new branch of Konveksi sensitivity of four variables, including sensitivity to decreasing demand levels, decreasing product selling prices, decreasing, increasing raw material costs, and increasing direct labor and indirect labor costs. Can identify the risks of opening a new branch of Konveksi XYZ in Bandung City with a percentage of 4.9%, and for entrepreneurs, it can be used as a consideration in making decisions in the business of opening a new branch of Konveksi. Based on the results of a feasibility study carried out taking into account market aspects, technical aspects and financial aspects, opening a new branch at XYZ Convection in Bandung City is feasible.